Chromatography of Solanum habrochaites extracts with the first record of the docosanoate, hexadecanoate and octadecanoate ethyls in this plant and in Solanaceae - Santos, C. A. M.; Teixeira, D. L.; Salgado-Neto, G.; Wilcken, C. F. [UNESP]; Lemes, P. G.; Tavares, W. S.; Sabattini, J. A.; Zanuncio, J. C. (FapUNIFESP (SciELO), 2024)
The increasing need for sustainable alternatives to synthetic insecticides has driven the analysis of extracts from Solanum habrochaites, a wild tomato, through fractionated column chromatography. Potential bioactive compounds for pest management, a clean and promising biotechnological solution, have been reported from this plant. The objective is to provide detailed gas chromatography data, including peaks, structural formulas, and retention indices for the extracts of S. habrochaites aerial parts. Column chromatographic analysis was conducted with five fractions (F1, F2, F5, F3, and F4) of S. habrochaites extracts. Long-chain hydrocarbons such as hexadecanoic acid and docosano were identified in the F1 fraction; fatty acid esters, including hexadecanoate and octadecenoate ethyls in the F2 and methyl ketones, with tridecan-2-one as the major component in the F5, while no identifiable compounds were disclosed in the F3 and F4 fractions. The column chromatography provided valuable insights into compounds in the F1, F2, and F5 fractions of S. habrochaites extracts, highlighting fatty acid esters, long-chain hydrocarbons, and methyl ketones. The bioactive compounds, from extracts of this plant, including the first record of the docosanoate, hexadecanoate and octadecanoate ethyls in S. habrochaites and Solanaceae, reinforces their promising biological application in different areas of science.